PROCESS ORIENTED GUIDED INQUIRY LEARNING, PEMBELAJARAN VAN HIELE, DAN KETERKAITANNYA - Desrina Hardianti; Dwi Desmayanasari; Noprisa Noprisa (ALGORITMA: Journal of Mathematics Education, 2020)
This research is a descriptive research. The purpose of this research was to analyze the relationship between  POGIL model and van Hiele learning in an effort to increase the level of students' geometrical thinking. This research was implemented in one of junior high school in Bandung. The population in this research was grade VII students. The sample consisted of 63 students. Data level of students' geometrical thinking obtained through test techniques. Test questions are arranged based on indicators from each level. The data collection technique was carried out using the triangulation method. The data analysis technique was descriptive. Steps in this research are identifying the problem, reviewing the literature, arranging the instrument, collecting the data, analyzing the data and making the conclussion. This research shows the relation betwenen POGIL model and van Hiele Learning. They are (1) engage dan elicit steps in POGIL discribes inquiry step in van Hiele learning, (2) explore step discribes direct orientation step, (3)  explanation step discribes explication step, (4) elaborate & extend steps discribes orientation step, (4) evaluation step discribes integration step.